BROILER CHICKEN PERFORMANCE BY SIRIH LEAF EXTRACT (Piper betle) IN DRINKING WATER - Anggeraini, Firdha; Sandiah, Natsir; Ba’a, La Ode (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
The objective of this experiment was to evaluate the effect of betel leaf on broiler performance.    Eighty DOC broilers of SR 707  strain during  28 days of the experiment.  eighty DOC broilers were placed randomly in 20 plots cages litter systems-sized swath of 1 x 1 x 0,6 m. The treatment consists of five degree-granting betel leaf extract that is T1 (Without betel leaf extract), T2 (betel leaf extract 0,5%/liter of drinking water),  T3 (1%/extract of betel leaf/liter of drinking water), T4 (betel leaf extract 1,5%/liter of drinking water),  T5 (betel leaf extract 2%/liter of drinking water). The parameters observed were broiler Performance that includes daily ration consumption, an increase of weight daily rations, and conversions.  The research grant of betel leaf extract via drinking water to the extent of 2% does not affect or have yet to produce a better performance than the normal treatment. Use of betel leaf extract dosage of 2% yield increase in weight and a good feed conversion rate.